Exploring Pakistani Physicians' Knowledge and Practices Regarding High Alert Medications: Findings and Implications - Mustafa, Zia Ul; Haroon, Shahzaib; Aslam, Naeem; Saeed, Ahsan; Salman, Muhammad; Hayat, Khezar; Shehzadi, Naureen; Hussain, Khalid; Khan, Amer Hayat (Frontiers in Pharmacology, 2022)
Introduction: Whilst many low-middle income countries (LMICs), including Pakistan, try and ensure patient safety within available resources, there are considerable concerns with medication use. Unsafe and inappropriate medication use, especially high alert medications (HAMs), is one of the important factors compromising patient safety and quality of care. Besides economic loss, HAMs contribute to greater morbidity, hospitalization, and mortality. Physicians as key members of the provision of healthcare are expected to be well aware of the administration and regulations surrounding HAMs. However, the current status is unknown in Pakistan. Consequently, the objectives of this study were to evaluate the knowledge of Pakistani physicians about the administration, regulation, and practices related to HAMs. This builds on our recently published study with nurses. Methods: An online cross-sectional study design was used and data were gathered from the physicians throughout Pakistan using previously used self-administered questionnaires during a period of five months (1st Jan-30th May 2021). All data were entered and analyzed using SPSS 22 for Windows. Results: 847 physicians provided consent were enrolled in the study. Most physicians (62.2%) were male, aged between 25-30 years (75.2%) and had 2–5-year’s work experience (50.9%). 27% were working in the emergency departments. The median (IQR) knowledge score for HAMs administration and regulation was 5 (3) and 5 (2), respectively. 46.4% of respondents were found to have moderate knowledge of HAMs; with increasing age, work experience and higher qualifications significantly associated (p<0.05) with better HAMs knowledge. Around 58% had good practices relating to HAMs during their routine work. Median practice scores increased significantly (p<0.05) with age, work experience and postgraduate qualification. Conclusion: Most Pakistani physicians possess moderate knowledge of HAMs administration and regulations. However, their practices relating to the HAMs administration and regulations are typically sub-optimal. Consequently, HAMs awareness needs to be improved by including course content in current curriculum, provision of hospital-based continuous training programs about patient safety and care, and establishment of multi-disciplinary health care teams, including board certified pharmacists and specialized nurses, for the effective execution of medication use process in Pakistani hospitals in the future.